PEMBERDAYAAN MASYARAKAT DALAM PEMBUATAN KERUPUK DAN PERMEN JAHE DARI AMPAS KELAPA DI KELURAHAN GAMBIR BARU KECAMATAN KISARAN TIMUR - Japina, Henky; Widya, Heni; Bina, Al (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
This community service activity aims to provide training to housewives in Gambir Baru Village, Kisaran Kota District, in processing coconut dregs into crackers and ginger candy. The methods applied in this activity include training in making crackers and ginger candy from coconut dregs, interviews with the community, and observations of environmental conditions and participants' readiness to participate in the training. The implementation of the activity includes several stages, namely location surveys, training implementation, and evaluation. The results of the training showed that participants experienced increased skills in processing coconut dregs into food products. In addition, this activity also opens up opportunities for the community to develop small businesses based on local raw materials. The evaluation carried out through product assessments and questionnaires showed that most participants understood the techniques for making crackers and ginger candy, although further assistance was still needed in terms of marketing and packaging so that the products were competitive in the market. With this training, it is hoped that the community can make optimal use of coconut dregs waste, reduce household waste, and create sustainable business opportunities. Advanced training on digital marketing and business management is recommended so that coconut pulp-based products can develop more widely and provide a greater economic impact for the local community